PARTICULAR MORPHOLOGICAL, MICROBIOLOGICAL, BIOCHEMICAL DATA OF ORAL AND KREVIKULAR FLUIDES IN CLINICALLY HEALTHY DOGS - Мірзаєва, М. С. (Scientific Progress & Innovations, 2013)
The results of laboratory tests of oral and krevicular fluids and in clinically healthy dogs (morphological composition, microbiological and biochemical parameters). On the basis of comprehensive studies of the referred to above substrates it has been satisfied: the number and species of microorganisms landform, clarified cellular composition (percentage: desquamative pavement epithelium, leukocytes - lymphocytes, neutrophils and salivary corpuscles), biochemical parameters: aspartate aminotransferase activity, alanine aminotransferase, alkaline phosphatase, lysozyme, and also the contents of crude protein, cholesterol, whole calcium, electrolytes (sodium, potassium, chloride) and pH.